2022
DOI: 10.1177/17470218221092590
|View full text |Cite
|
Sign up to set email alerts
|

The impact of briefly observing faces in opaque facial masks on emotion recognition and empathic concern

Abstract: Since the outbreak of SARS-CoV-2 in 2019, there have been global public health initiatives that have advocated for the community use of face masks to reduce spread of the virus. Although the community use of facial coverings has been deemed essential for public health, there have been calls for enquiries to ascertain how face masks may impact non-verbal methods of communication. This study aimed to ascertain how the brief observations of faces in opaque facial coverings could impact facial emotion recognition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 92 publications
1
8
0
Order By: Relevance
“…Contrary to our results, researchers have found other aspects of empathy to be related to the identification of emotion in masked or unmasked facial expressions. Israelashvili and colleagues (2020) found a positive relationship between unmasked facial emotion recognition scores and higher empathic concern, and a negative association with personal distress; a similar pattern was reported by Shepherd and Rippon (2022) that found a positive relationship between masked facial emotion recognition scores and higher empathic concern. Schreckenbach et al (2018) using unmasked DANVA2-faces found that “simulated” patients who were extraverted rated medical students who were more accurate in identifying emotions in faces as more empathetic.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Contrary to our results, researchers have found other aspects of empathy to be related to the identification of emotion in masked or unmasked facial expressions. Israelashvili and colleagues (2020) found a positive relationship between unmasked facial emotion recognition scores and higher empathic concern, and a negative association with personal distress; a similar pattern was reported by Shepherd and Rippon (2022) that found a positive relationship between masked facial emotion recognition scores and higher empathic concern. Schreckenbach et al (2018) using unmasked DANVA2-faces found that “simulated” patients who were extraverted rated medical students who were more accurate in identifying emotions in faces as more empathetic.…”
Section: Discussionsupporting
confidence: 73%
“…While most researchers have found that masked faces made identifying emotions generally more difficult than unmasked ones, some also have found a lack of the wearing of masks to make no difference in identifying specific emotions. For example, Shepherd and Rippon (2022) found that though facemasks significantly reduced accuracy in the recognition of disgust, fear, happiness, sadness, and surprise, they did not so for anger. This last finding in Shepherd and Rippon's study may be due to the fact that disgust was often mistakenly perceived as anger (which accounted for 20% of the total misattribution in the study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with great interest the recent study performed by Shepherd and Rippon (2023) which addresses a pertinent point of view regarding how the broad use of face masks affects significant reductions in emotion recognition such as disgust, fear, happiness, sadness, and surprise when people are exposed to facial stimuli for a brief period of time. The authors accessed 199 participants and evaluated their ability to recognise emotions on masked faces and face stimuli with no mask, showing the least accuracy of identifying the emotion of fear within the masked condition, but also with low accuracy in identifying sadness and disgust when compared with unmasked faces.…”
mentioning
confidence: 99%
“…The study performed by Shepherd and Rippon (2023) brought an analysis of the influence of the use of face masks on the ability to recognise facial expressions; however, our concern is whether the results of studies, such as those by Shepherd and Rippon, can impact the use of masks and what would be the best way to disseminate such results so as not to discourage the prolonged use of these personal protective equipment. This restlessness is increased with studies like Huang et al (2021) that investigated data from 1,993 online questionnaires about COVID-19 and perceptions of effectiveness and mask use in a population in a midwestern US state and found that if respondents did not believe masks were useful, they were 40 times more likely not to use this type of personal protective equipment.…”
mentioning
confidence: 99%